Pendidikan Karakter dalam Lingkungan Wanita Karir - Nurhayati Sahibe; Munirah Munirah (Jurnal Ilmiah Iqra', 2021)
Character Education in Career Women. This article aims to reveal the problems of character education in the family environment, character education has the longest process in the family, and the behavioral problems of children encountered in the field. The method used is a literature review, which is one of the existing research methods, namely reviewing literature sourced from relevant books, articles. The literature review is taken from literature studies related to the problem being studied. The findings show that good character education will form a person who is virtuous, professional, and able to make decisions objectively